Cytotoxicity of α-mangostin encapsulated polymeric nanoparticles against lung cancer cells - Mai Phuong, Nguyen Thi; Lam, Tran Dai; Mai, Ta Thu; Hop, Nguyen Trung (Academia Journal of Biology, 2018)
Alpha-Mangostin (AMG) isolated from Garcinia mangostana L., has been intensively reported to possess potent anti-cancer properties. However its clinical application is limited due to poor aqueous-solubility. Here, we successfully synthesised and characterised water-soluble ß-cyclodextrin-coated AMG (NMG) with size of <50 nm and zeta potential of -38 mV. The changes in spectra of NMG compared to NMG suggested an interaction between AMG and the carrier ß-cyclodextrin. Similar cytotoxic activities against lung cancer cells A549 of water-soluble NMG and organic-solvent soluble AMG were found with IC50 of 2.34 and 4.86 µg/ml, respectively. Moreover, observation under fluorescent microscopy indicated that NMG was taken up into the cancer cells and clearly affected nuclear morphology. The obtained data demonstrates that the synthesized NMG improves bioavailability of AMG while maintains its anti-cancer activity. Citation: Nguyen Thi Mai Phuong, Tran Dai Lam, Ta Thu Mai, Nguyen Trung Hop, 2018. Cytotoxicity of α-mangostin encapsulated polymeric nanoparticles against lung cancer cells. Tap chi Sinh hoc, 40(1): 108-114. DOI: 10.15625/0866-7160/v40n1.10504. *Corresponding author: phuongnguyenibt@gmail.com Received 7 November 2018, accepted 12 March 2018